Exploring Fry and Drew’s application of Ghanaian symbolism in architectural ornamentations: Case study of Opoku Ware and Prempeh Senior High Schools in Kumasi, Ghana (Journal of Science and Technology, 2022)
Ghanaian art forms are dominated by symbolism that characterises the socio-cultural, religious and political ideals of the people. These symbols which are often used in religious, and socio-political buildings for educational, aesthetic and religious purposes encapsulate Ghanaian thoughts, beliefs, ideas, aspirations and spirituality in abstract forms. The objective of this study is to explore the significance, philosophical and socio-cultural narratives embodied in the symbols that are employed in the architectural ornamentation of Maxwell Fry and Jane Drew's architectural project in Opoku Ware Senior High and Prempeh Senior High Schools in Kumasi. This study employed the qualitative method of research using observation, library research and photographic documentations. The data were analysed using the interpretivist research method. The results of the study show that Fry and Drew's application of Ghanaian symbols in school architecture at Opoku Ware Senior High and Prempeh Senior High Schools in Kumasi exemplify their response to contextualising indigenous sensibilities in design. The symbols which were mainly the stool, crocodile from the adinkra symbology and honey comb motifs were generally employed as precast concrete for the dual purpose of serving practical and aesthetics demands of the schools' architecture. The study concludes that the stool, crocodile and honey comb motifs symbolise authority, status, power, versatility and assiduousness, and their deployment in the architecture of these two schools is a negotiation of the Ashanti Royal authority and symbolic power that is derived from western academic experience.